Hsp27, a potential EcR target, protects nonylphenol-induced cellular and organismal toxicity in Drosophila melanogaster. (15th January 2022) - Dwivedi, Shiwangi; D'Souza, Leonard Clinton; Shetty, Nidhi Ganesh; Raghu, Shamprasad Varija; Sharma, Anurag
Abstract: Deciphering the potential mechanism of chemical-induced toxicity enables us to alleviate the cellular and organismal dysfunction. The environmental presence of nonylphenol (endocrine disruptor) has a major health concern due to its widespread usage in our day-to-day life. The current study establishes a novel functional link among nonylphenol-induced oxidative stress, Heat shock protein 27 ( Hsp27, member of stress protein family), and Ecdysone receptor ( EcR, a nuclear receptor), which eventually coordinates the nonylphenol-induced sub-cellular and organismal level toxicity in a genetically tractable model Drosophila melanogaster . Drosophila larvae exposed to nonylphenol (0.05, 0.5 and 5.0 μg/mL) showed a significant decrease in Hsp27 and EcR mRNA levels in the midgut. In concurrence, reactive oxygen species (ROS) levels were increased with a corresponding decline in glutathione (GSH) level and Thioredoxin reductase (TrxR) activity. Increased lipid peroxidation (LPO), protein carbonyl (PC) contents, and cell death were also observed in a correlation with the nonylphenol concentrations. Sub-cellular toxicity poses a negative organismal response, which was evident by delayed larval development and reduced Drosophila emergence. Subsequently, a positive genetic correlation ( p < 0.001) between EcR and Hsp27 revealed that nonylphenol-dependent EcR reduction is a possible link for the downregulation of Hsp27 . Further, Hsp27 overexpression in midgut cells showed a reduction in nonylphenol-induced intracellular ROS, LPO, PC content, and cell death through the TrxR mediated regenerative pathway and reduced GSH level improving the organismal response to the nonylphenol exposure. Altogether, the study elucidates the potential EcR - Hsp27 molecular interactions in mitigating the nonylphenol-induced cellular and organismal toxicity. Graphical abstract: Image 1 Highlights: Nonylphenol exposure downregulates Hsp27 and EcR expression in Drosophila midgut. EcR regulates the expression of Hsp27 in normal and nonylphenol-exposed condition. Nonylphenol induces oxidative stress resulting in cellular and organismal toxicity. Hsp27 -overexpression offers systemic shield by regulating GSH-regenerative pathway.